x(x+1)=x+23

Simple and best practice solution for x(x+1)=x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+1)=x+23 equation:



x(x+1)=x+23
We move all terms to the left:
x(x+1)-(x+23)=0
We multiply parentheses
x^2+x-(x+23)=0
We get rid of parentheses
x^2+x-x-23=0
We add all the numbers together, and all the variables
x^2-23=0
a = 1; b = 0; c = -23;
Δ = b2-4ac
Δ = 02-4·1·(-23)
Δ = 92
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{92}=\sqrt{4*23}=\sqrt{4}*\sqrt{23}=2\sqrt{23}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{23}}{2*1}=\frac{0-2\sqrt{23}}{2} =-\frac{2\sqrt{23}}{2} =-\sqrt{23} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{23}}{2*1}=\frac{0+2\sqrt{23}}{2} =\frac{2\sqrt{23}}{2} =\sqrt{23} $

See similar equations:

| 5-(1+m)=6(m-4) | | -147=7x+3(-6x-5) | | 24=4+10x | | 1/2(8x+10)=1/3(15x+15) | | 2|x+2|+8=10 | | 6x+3=(3x+5) | | G(x)=x4-4x | | 2n^2-20n+20=0 | | 2.4x-14=19 | | 5m+10=5m+9 | | -9(t+-2)=4(t-15) | | 6x+3(4+x)=18 | | 3y+9=2y-9= | | 2x=360÷4 | | F(x)=x3-3x | | 3x5.2=2-5x | | (x+3)^2=9 | | 10x^2+6x+20=0 | | 3(5z-(3))-(4(2z+1))=5z-(2) | | 2(2y-4)+12=-y+8+5y | | F(x)=x5+5x | | (5.15-2x)x(7.65-x)=0 | | 1/2(3x+4)=3+2 | | 6x-3(x-5)=-(2x+15) | | -4(2n-5=-28 | | 5(3-d)=2+1 | | 9/8=3w/24 | | 12x^2-10x-28=0 | | 28+8x=8(x+3) | | x^(2/3)+9x^(1/3)+8=0 | | -9/8=3w/24 | | 23=3n-7 |

Equations solver categories